Potency of bioactive compounds in Minasarua traditional beverage from Indonesia as an antioxidant and anti-inflammatory: A review - Maramy, Neyla Vista; Widyaningsih, Tri Dewanti; Martati, Erryana; Endharti, Agustina Tri (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Minasarua is a traditional beverage believed by the local community in Bima, Indonesia, to have perceived health benefits. This review explores the potential of bioactive compounds in Minasarua as antioxidants and anti-inflammatories. The product is made from ingredients such as ginger (Zingiber officinale), turmeric (Curcuma longa), Javanese chilli pepper (Piper retrofractum Vahl), pepper (Piper nigrum), and fermented black glutinous rice, each of which contributes key bioactive compounds, including gingerol, shogaol, curcumin, piperine, and anthocyanins. These compounds are known for their ability to neutralize free radicals and inhibit the expression of pro-inflammatory cytokines. Although individual components have been studied extensively, the potential synergistic effects of these compounds when combined in Minasarua remain underexplored. This review highlights the promising role of Minasarua as a functional beverage, suggesting that the interaction among its major compounds may enhance their collective antioxidant and anti-inflammatory activities. These findings offer a foundation for future research into the development of Minasarua as a health-promoting traditional drink.